The signification levels of scenery in the Iraqi theatrical show (the play of alubah for example) (Al-Academy, 2017)
Signification with its different aspects constitutes various aesthetic pictures for human and nature creations over different periods of time. It was a focal around which logical thinking loops on the interpretation level of the signification movement according to its structural context expresses its hidden entities with which a human being deals according to two symmetrical levels while interpreting to attain meaning. Sense was the first passing window for the picture of signification which thought deals with. While trying to decode it and because art in general and theatre in particular are considered as the basis of creating signification through its visual and aural elements, so it was necessary to consider one of the elements of creating the visual signification, namely the theatrical scene through which the receiver knows the nature, type, and the events of the show. This is to specify the research line to identify its goals on the level of signification of the theatrical show. To arrive at these points, it was imperative to specify an epistemological path fulfilling this, thus the theoretical framework was composed of three sections. The first section, semiology, deals with its origin and concept. The researcher surveys the origin of signification historically and its rise as a science with its basics and rules through which it identifies the understanding context. This context of understanding matches the line of epistemological research. The second is entitled as the elements of optical modulation in the theatrical show where the researcher draws the map of the signification dimensions of the elements of optical modulation that are used in the architecture of the scene as a ideological and aesthetic unit. The third section is entitled as the ways of designing the scene in the theatrical show. The researcher has discussed the schools of the technical designing of the theatrical scene in the middle of the environment of the show. After presenting the epistemological map for these sections. The researcher has created norms by which he analyzed the research. Thus, the researcher concluded the following results;(1) the theatrical scene has presented symbolic information constituting integrating relationship with the other visual elements system giving it an additional identity in producing meaning which sparks the receivers mind in inducing the various signification dimensions which were established by the theatrical show, (2) the theatrical scene has achieved multi-level interpretative readings which helps producing the signification dimensions that match the show thinking aesthetically and intellectually This finalized the research where the researcher addressed some conclusions for example, (1) the designer adopted the elements of optical modulation to show the signification dimensions for the theatrical scene, (2) the interpretation level of the theatrical scene formations and workings is considered the outstanding feature of identifying the signification dimensions for the events environment in the theatrical show. Finally, the researcher gave his list of references